2016
DOI: 10.1007/s10439-016-1633-3
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-ene Clickable Poly(glycidol) Hydrogels for Biofabrication

Abstract: In this study we introduce linear poly(glycidol) (PG), a structural analog of poly(ethylene glycol) bearing side chains at each repeating unit, as polymer basis for bioink development. We prepare allyl- and thiol-functional linear PG that can rapidly be polymerized to a three-dimensionally cross-linked hydrogel network via UV mediated thiol-ene click reaction. Influence of polymer concentration and UV irradiation on mechanical properties and swelling behavior was examined. Thiol-functional PG was synthesized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 32 publications
0
98
0
3
Order By: Relevance
“…PG is chemically closely related to PEG and biologically similarly inert but provides the possibility of a higher functionalization density due to side chain functionalization . This is also true for PG‐based hydrogels, as we were able to show recently by utilizing thiol‐ and allyl‐modified PG for the generation of thiol‐ene clickable PG hydrogels. By replacing the thiol‐modified PG component with bioactive thiol‐modified HA, the deposition of cartilage‐specific matrix components secreted by encapsulated MSCs, was significantly improved when compared to pure PG hydrogels .…”
Section: Resultsmentioning
confidence: 60%
“…PG is chemically closely related to PEG and biologically similarly inert but provides the possibility of a higher functionalization density due to side chain functionalization . This is also true for PG‐based hydrogels, as we were able to show recently by utilizing thiol‐ and allyl‐modified PG for the generation of thiol‐ene clickable PG hydrogels. By replacing the thiol‐modified PG component with bioactive thiol‐modified HA, the deposition of cartilage‐specific matrix components secreted by encapsulated MSCs, was significantly improved when compared to pure PG hydrogels .…”
Section: Resultsmentioning
confidence: 60%
“…P(AGE‐ co ‐G) was synthesized via anionic polymerization of AGE and EEGE in bulk as reported before . Briefly, for polymerization, AGE (6.30 mmol) and EEGE (54.0 mmol) were mixed with the initiator KO t Bu (1.00 mmol) under inert atmosphere and stirred at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this promising chemistry has so far not been applied for biofabrication. We have recently reported the synthesis of allyl‐ and thiol‐functionalized polyglycidols (PG) and the application of this system together with hyaluronic acid as rheological additive with beneficial bioactivity for biofabrication . We further discuss this system here as well as future possibilities of this approach within biofabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Photo‐crosslinking systems are widely used in biofabrication, as they offer rapid and on demand triggering of the polymerization reaction. Early biofabrication approaches have utilized photoinitiators, like Irgacure 2959, that rely on ultraviolet (UV) light to generate radicals, which induce the crosslinking reaction . As UV light can potentially be harmful for cells, the irradiation dose should be limited and several studies have indeed identified irradiation times that permit preservation of cell viability and functionality .…”
Section: Recent Progress For Controlling Shapementioning
confidence: 99%